THE AGRICULTURAL SITUATION IN THE SAMARKAND REGION IN THE SECOND HALF OF THE 19TH CENTURY – THE BEGINNING OF THE 20TH CENTURY (Scientific journal of the Fergana State University, 2023)
During the colonial period, the agrarian sector and the essence of the Samarkand region were reformed. The article defines the reforms of the Russian Empire in the second half of the 19th – early 20th centuries in the field of agriculture in the Samarkand region, statistical data and materials on crops, types of crops and the impact of cotton expansion on agriculture. An assessment is also given of the impact of the changes and innovations carried out by the Russian administration in this area in the historical period when the region was called the Zeravshan okrug, and then the Samarkand region. At the same time, statistical data on sown areas and yields in the region were taken into account.